Transport and partitioning of metals in river networks of a plain area with sedimentary resuspension and implications for downstream lakes. (1st February 2022) - Zhang, Jin; Wang, Kun; Yi, Qitao; Zhang, Tao; Shi, Wenqing; Zhou, Xuefei
Abstract: This study showed that metal transport and partitioning are primarily controlled by suspended solids with seasonal flow regimes in plain river networks with sedimentary resuspension. Eight metal species containing iron (Fe), manganese (Mn), cadmium (Cd), chrome (Cr), copper (Cu), nickel (Ni), lead (Pb), and zinc (Zn), in multiple phases of sediments, suspended solids (>0.7 μm), colloids (1 nm-0.7 μm) and dissolved phase (<1 nm) were analysed to characterize their temporal-spatial patterns, partitioning and transport on a watershed scale. Metal concentrations were associated with suspended solids in the water column and decreased from low flow to high flow. However, metal partitioning between particulate phase (suspended solids) and dissolvable phases (colloids and dissolved phase) was reversed and increased from low flow to high flow with decreased concentration of total suspended solids and median particle size. Partition coefficients ( k p ) showed differences among metal species, with higher values for Pb (354.3–649.0 L/g) and Cr (54.2–223.7 L/g) and lower values for Zn (2.5–25.2 L/g) and Cd (17.3–21.0 L/g). Metal concentrations in sediments increased by factors of 1.2–3.0 from upstream to downstream in watersheds impacted by urbanization. The behaviours of metals in rivers provide deeper insight into the ecological risks they pose for downstream lakes, where increased redox potential and organic matter may increase metal mobility due to algal blooms. Areas with heavy pollution of metals and the transport routines of metals in the river networks were also revealed in our research. Graphical abstract: Image 1 Highlights: Particles are sorted during sediment resuspension and transported with flow regime. Suspended solids controlled metal partitioning in turbid water of river networks. Partition coefficients of Pb and Cr were higher than that of Cd and Zn. Metal mobility in downstream lakes was linked to their behaviour in upstream rivers.